O uso do Cadastro Único como instrumento de avaliação de uma política pública para mulher: o caso do CMais Sergipe - Alves, Jociara Batista (2024)
Objective: to describe the profile of beneficiaries of the “C Mais Mulher Program” based on data from CadÚnico. The work is aligned with PROFIAP's line of research in Public Policies, focusing on the evaluation and improvement of a government program aimed at combating violence against women. Methodology: qualitative and quantitative case study, using descriptive statistics to profile the beneficiaries; evidence collection was carried out through face-to-face interviews, using a semi- structured script. Main results: the results indicate that women victims of violence who accessed the C Mais Mulher program are predominantly young, up to 34 years old. The largest proportion of beneficiaries resides in the Agreste (16.72%) and Central South (16.14%) regions of Sergipe. Furthermore, the women served by the program belong to families with lower incomes compared to those in CadÚnico, and these families have, on average, around 3 members. These family units are the poorest among those already vulnerable. Regarding educational level, 33.9% of women enrolled in the program have completed high school, while a significant percentage of 46.44% interrupted their studies in the eighth grade. Relevance and Originality: the relevance of the work lies in using statistical analysis and mapping of data from the Single Registry to identify patterns and improve the focus of public policies to combat violence. Its originality lies in the application of this data to evaluate and improve the "C Mais Mulher Program". Social/societal contributions: The data obtained offers a solid foundation for improving the “C Mais Mulher Program”, allowing managers and public policy makers to better understand the profile of beneficiaries and their specific needs, the research can guide the allocation of resources and the intensification of actions in areas that require more attention, enhancing the effectiveness of the program.